Riba al-Nasiah i riba al-Fadl, czyli Koran i sunna o lichwie - Szwagiel, Patryk (Katedra Doktryn Politycznych i Prawnych Wydziału Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego, 2022)
Riba can roughly be translated as usury, a practice leading to unfair and unethical enrichment of a lender at the expense of the debtor, who is charged excessive interest. The significance of riba in Islam has been discussed for ages, and today in the times of the growing Islamic financial market, Muslim scholars are faced with the need to adjust the prohibition to the contemporary realities. The doctrine contains various definitions of the term riba as well as numerous conflicting approaches to the objective and subjective scope of the prohibition of usury. Whether the prohibition is perceived as an objection to exploitation of the poor, or contradiction of charity, or simply a manifestation of the differences in the understanding of the definition of money, riba is morally condemned by all Muslim theologians.